Implications for ozone control by understanding the survivor bias in observed ozone-volatile organic compounds system - Zhenyu Wang (npj Climate and Atmospheric Science, 2022)
Abstract Tropospheric ozone (O3) affects Earth’s climate and human health. Volatile organic compounds (VOCs), major contributors to O3 formation, are of particular interest. Generally, the measured concentrations of VOCs (M-VOCs) and O3 show nonlinear or even opposite time serial-trend. We attributed the phenomenon to survivor bias: lack of insight of the photochemically consumed VOCs (C-VOCs) which emitted from sources to ambient and devote to forming O3, while excessive concern on the measured VOCs (M-VOCs) at observation site. Both observational and model results provide evidence that C-VOCs are the key to O3 formation. We proposed an improved model to quantify the source contributions of C-VOCs (biogenic emissions, gasoline evaporation, industry, etc.) and their impacts on the formation of O3, successfully avoiding the misidentification of dominant VOCs sources originated from the survivor bias in observational data. The survivor bias found in this study highlights that focusing of M-VOCs directly is insufficient and demonstrates the necessity of capture the sources of C-VOCs which contribute to O3 formation.